2001
DOI: 10.1046/j.1469-7580.2001.19910195.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of positioning and identification of vertebrate limbs

Abstract: Emerging developmental studies contribute to our understanding of vertebrate evolution because changes in the developmental process and the genes responsible for such changes provide a unique way for evaluating the evolution of morphology. Endoskeletal limbs, the locomotor organs that are unique to vertebrates, are a popular model system in the fields of palaeontology and phylogeny because their structure is highly visible and their bony pattern is easily preserved in the fossil records. Similarly, limb develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…8E,E 0 ). These ectopic limb buds would be expected to give rise to an additional limb skeleton in the flank, according to previous reports (Ohuchi et al, 1997;Yonei-Tamura et al, 1999;Tamura et al, 2001). In a typical sample (Fig.…”
Section: Effect Of Fgf Signaling On Apoptosis In the Flank Lpmsupporting
confidence: 66%
“…8E,E 0 ). These ectopic limb buds would be expected to give rise to an additional limb skeleton in the flank, according to previous reports (Ohuchi et al, 1997;Yonei-Tamura et al, 1999;Tamura et al, 2001). In a typical sample (Fig.…”
Section: Effect Of Fgf Signaling On Apoptosis In the Flank Lpmsupporting
confidence: 66%
“…Cohn et al,'95). YoneiTamura et al (2008) demonstrated that this continuous lateral competency also occurred in the zebrafish and dogfish shark, and also that a dorsal competency strip could be artificially created dorsally in turtle and mouse (already been shown in the chick; Yonei- Tamura et al, '99;Tamura et al, 2001). Along with this, Yonei-Tamura et al (2008) showed that anteroposterior patterning was a feature in chondrichthyan fins, again as a common gnathostome feature.…”
Section: Similarity Between Unpaired and Paired Finsmentioning
confidence: 87%
“…In contrast, other recent ideas suggest that an ancestral vertebrate had a single pair of fins; either posterior 11 or anterior 12 . In tetrapods and teleosts, the identity of each pair of appendages is determined by expression of T-box genes Tbx5 and Tbx4, which are expressed in the anterior and posterior appendages, respectively 13 . In contrast, the cephalochordate Amphioxus has only one such gene, AmphiTbx4/5 (ref.…”
mentioning
confidence: 99%
“…The Tbox region alignment provides further evidence that ScTbx4 and ScTbx5 belong to Tbx4 and Tbx5 subfamilies respectively. Skate embryos may also have a Tbx5 gene 13 . In stage 28 dogfish embryos, ScTbx5 expression was observed in pectoral fin buds (Fig.…”
mentioning
confidence: 99%